2013
DOI: 10.1152/ajpgi.00154.2012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive Cl secretion in biliary epithelium mediated through TMEM16A

Abstract: Bile formation by the liver is initiated by canalicular transport at the hepatocyte membrane, leading to an increase in ductular bile flow. Thus, bile duct epithelial cells (cholangiocytes), which contribute to the volume and dilution of bile through regulated Cl(-) transport, are exposed to changes in flow and shear force at the apical membrane. The aim of the present study was to determine if fluid flow, or shear stress, is a signal regulating cholangiocyte transport. The results demonstrate that, in human a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 44 publications
1
55
0
Order By: Relevance
“…Cholangiocytes possess cilia on their apical surface that act as mechanoreceptors, chemosensors, and osmosensors 38 . Shear stress along the apical membrane of cholangiocytes is detected by cilia, resulting in upregulation of Cl − currents via TMEM16A (aka anoctamin), a Ca 2+ -activated Cl − channel 39 . This process is dependent on PKC-α, extracellular ATP, purinergic P2 receptors, and increases in intracellular Ca 2+ concentration 39 .…”
Section: Mechanisms and Regulators Of Cholangiocyte Proliferationmentioning
confidence: 99%
See 2 more Smart Citations
“…Cholangiocytes possess cilia on their apical surface that act as mechanoreceptors, chemosensors, and osmosensors 38 . Shear stress along the apical membrane of cholangiocytes is detected by cilia, resulting in upregulation of Cl − currents via TMEM16A (aka anoctamin), a Ca 2+ -activated Cl − channel 39 . This process is dependent on PKC-α, extracellular ATP, purinergic P2 receptors, and increases in intracellular Ca 2+ concentration 39 .…”
Section: Mechanisms and Regulators Of Cholangiocyte Proliferationmentioning
confidence: 99%
“…Shear stress along the apical membrane of cholangiocytes is detected by cilia, resulting in upregulation of Cl − currents via TMEM16A (aka anoctamin), a Ca 2+ -activated Cl − channel 39 . This process is dependent on PKC-α, extracellular ATP, purinergic P2 receptors, and increases in intracellular Ca 2+ concentration 39 . Inhibition of CFTR did not change flow-stimulated currents in their studies, suggesting a different mechanism of Cl − transport when cholangiocytes are exposed to shear forces 39 .…”
Section: Mechanisms and Regulators Of Cholangiocyte Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although less well known, the occurrence of P2-type receptors at the basolateral domain of cholangiocytes has also been reported [14,15]. By acting on these P2 receptors ATP triggers an increase in intracellular Ca 2+ , which results in the activation of K + and Cl À channels [16].…”
Section: Introductionmentioning
confidence: 98%
“…Various in vitro loading techniques, such as cell swelling, substrate stretch loading and fluid shear stress (FSS), are used in the study of osteocyte response to mechanical stimulation. However, the majority of studies do not recapitulate osteoblast anabolism under mechanical stimulation, including the activation of intracellular chloride ions, chloride channel genes and channel proteins (3)(4)(5)(6)(7). In fact, studies have shown that numerous ion channels [such as Ca 2+ channels (8) and K + channels (9)] have a role in osteogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%